2021
DOI: 10.1177/23969873211047681
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of fatigue after stroke: A systematic review and meta-analysis

Abstract: Background and Purpose Post-stroke fatigue is a debilitating and long-lasting condition. However, there are uncertainties regarding its prevalence and variability between studies. This review aims to estimate the prevalence of fatigue and determine the factors responsible for its variation in the literature. Methods A systematic review was conducted for all published studies (search to November 2020) using AMED, CINAHL, EMBASE, MEDLINE, PsycINFO, SCOPUS and Web of Science. Papers were included if they recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 77 publications
4
38
2
2
Order By: Relevance
“…The incidence of PSF in the acute phase is 34.0 % in our study, which is in line with previous studies ( 7 11 ). This may be attributed to our rigorous and meticulous assessment about PSF during this prospective study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The incidence of PSF in the acute phase is 34.0 % in our study, which is in line with previous studies ( 7 11 ). This may be attributed to our rigorous and meticulous assessment about PSF during this prospective study.…”
Section: Discussionsupporting
confidence: 93%
“…Although there are many treatment options for ischemic stroke nowadays (4)(5)(6), the AIS patients may undergo several complications during their treatment and rehabilitation. Post-stroke fatigue (PSF), whose incidence range from 23 to 85%, is a common emotional complication after the onset of AIS (7)(8)(9)(10)(11). PSF could lead to poor recovery and prognosis (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Only three studies reported minor adverse effects that were reversed after treatment. Fatigue is one of the most common symptoms of post-stroke (Alghamdi et al, 2021 ). Most of the studies included in the meta-analysis had 30-min or longer interventions, and patients needed to maintain their attention during training, which tended to induce fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is associated with dependence in daily activities, poor quality of life ( 2 ), reduced physical activity ( 3 ), and increased morbidity and mortality ( 4 ). Approximately half of all stroke survivors experience fatigue ( 5 ), regardless of severity ( 6 ). Optimizing motor recovery post-stroke requires high-dose rehabilitation ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%